IMPACT OF HEARING AID USE ON AUDITORY PERCEPTION AND VERBAL SHORT-TERM MEMORY IN CHILDREN WITH BIMODAL STIMULATION - Ostojić, Sanja; Jotić, Ana; Nikolić, Mina; Mirić, Danica; Mikić, Branka (Specijalna edukacija i rehabilitacija, 2015)
Introduction: The combination of electric stimulation from cochlear implant (CI) with acoustic stimulation from hearing aid (HA), otherwise known as bimodal hearing, may provide several binaural benefits including binaural summation, binaural squelch, reduction of the head shadow effect, and improved localization. Purpose: This study investigated the influence of preoperative rehabilitation and bilateral HA use, bimodal stimulation post-implantation (CI on one ear and HA on the non-implanted ear) and hearing thresholds in the implanted and the non-implanted ear on auditory perception and verbal short-term memory. Method: Immediate verbal memory test for Serbian language consisting of four subtest was used for auditory perception testing on 21 pre-lingually deaf children. Results: Duration of bimodal hearing proved to be significant in the terms of auditory perception and verbal short-term memory. Mid- and high-frequency amplified thresholds on the non-implanted ear were correlated with poorer perception and reproduction of monosyllables and nonsense words. Conclusion: Duration of bimodal hearing proved to be significant in the terms of auditory perception, speech reproduction and semantic ability. Patients with a unilateral cochlear implant who have measurable residual hearing in the non-implanted ear should be individually fitted with a hearing aid in that ear, to improve speech perception and maximize binaural sensitivity. Key words: hearing aid, bimodal stimulation, auditory perception, short term memory